2006
DOI: 10.1136/jmg.2005.036350
|View full text |Cite
|
Sign up to set email alerts
|

Subtelomere FISH analysis of 11 688 cases: an evaluation of the frequency and pattern of subtelomere rearrangements in individuals with developmental disabilities

Abstract: This study of subtelomere rearrangements is a 20 fold increase in number over the previously reported largest study and represents an unbiased analysis of subtelomere rearrangements in a large, unselected patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
327
2
13

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(363 citation statements)
references
References 18 publications
21
327
2
13
Order By: Relevance
“…In accordance with the report by Ravnan et al 18 showing that the majority of chromosomal terminal deletions were de novo (48/60 familial studies), we confirmed in our series that, strictly speaking, no patient had inherited the 2q37 deletion from his/her parents. The 2q polymorphism is a common condition in the population (5%).…”
Section: Parental Analysissupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with the report by Ravnan et al 18 showing that the majority of chromosomal terminal deletions were de novo (48/60 familial studies), we confirmed in our series that, strictly speaking, no patient had inherited the 2q37 deletion from his/her parents. The 2q polymorphism is a common condition in the population (5%).…”
Section: Parental Analysissupporting
confidence: 93%
“…In the largest study of the kind, in which the telomeres of 11 688 individuals were investigated, the 2qtel subtelomeric deletion was a frequently encountered variation, observed in seven patients as a pure deletion. 18 In the study by Ravnan et al, near half of the phenotypically altered patients had terminal 2q deletions, but it was not explicitly indicated whether the 2q deletion was a deleterious del 2q37 or only the common polymorphism. Indeed, the first subtelomeric FISH probes used encompassed the polymorphic loci.…”
Section: Mappingmentioning
confidence: 99%
“…For the last three patients with 2pter deletion reported in the literature, clinical information was unavailable. 3,5 Clinical features of the patients reported in the literature are listed in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Becker et al 6 reported a patient with a de novo pure 2p25.2 deletion, bilateral severe talipes equinovarus, pulmonary valve stenosis, nasal polyps, mild psychomotor retardation, and overweightness with food seeking behaviour. Several patients were then reported presenting with obesity, intellectual disability (ID), and 2p25 deletion.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,8 The identification of patients with atypical 4p deletions has provided key insight into which regions of 4p16.3 may (or may not) contribute to the pathogenesis of WHS. For example, small terminal deletions (up to 400 kb) have been inherited from phenotypically normal individuals; [12][13][14] indicating that monosomy of this region is likely benign. 11 Between B1.8 and 2.0 Mb from the 4p terminus, two adjacent critical regions were proposed based on the smallest region of overlap (SRO) among the deletions of individuals with or without the core features of WHS.…”
Section: Introductionmentioning
confidence: 99%